Metabolome and transcriptomics analyses reveal quality differences between Camellia tachangensis F. C. Zhang and C. sinensis (L.) O. Kunzte. - Yunfei Xu; Qihang Zhou; Xinglin Wang; Xingpan Meng; Zhengdong Zhang; Xu Zhang; Ximin Zhang; Suzhen Niu; Guiping Chen; Lunxian Liu; Tie Shen (PLoS ONE)
Tea ranks among the top three most beloved non-alcoholic beverages worldwide and boasts significant economic and health benefits. In addition to Camellia sinensis (L.) O. Kuntze, and other Camellia plants in China are consumed by residents as tea drinks, which also have important economic value. The present study introduces one of the wild tea species, namely, Camellia tachangensis F. C. Zhang. We analyzed changes in metabolite abundance and gene expression patterns of C. tachangensis and C. sinensis using metabonomics and transcriptomics. We found 1056 metabolites, including 256 differential metabolites (67 upregulated and 189 downregulated). Additionally, transcriptome analysis revealed 8049 differentially expressed genes, with 4418 upregulated and 3631 downregulated genes. C. sinensis boasts a notable abundance of Amino acids, which can be attributed to its specific genetic makeup. In Theanine and Caffeine metabolic pathways, the levels of the majority of amino acids and caffeine tend to decrease. In Flavonoid biosynthesis, the levels of the Flavanone Fustin and Epicatechin are higher in C. tachangensis, while Epigallocatechin and Gallocatechin levels are higher in C. sinensis. This indicates that the metabolic components of C. sinensis and C. tachangensis are not identical, which may result in a unique flavor.